The social responsibility of television in the dissemination of a culture of tolerance and rejection of hatred (Applied Study on a Sample of the UAE Society 2019-2020) - Altaa, Mustafa; Al-rawashdeh, Alaa (Dirasat: Human and Social Sciences, 2021)
The research aims at identifying the social responsibility of television in demonstrating tolerance culture and rejection of hatred. The research reached a number of the most important results: that (51.5%) play an important role in the publication of the film tolerance and renounce hate, compared to (21.5%) (44.5%) of respondents in television are the most influential in spreading violence and hate speech, while (39%). Eighty-five percent of respondents on television channels are held responsible for spreading the culture of hatred, while 15 percent do not hold those responsible for television because they believe that the causes of hatred and violence are numerous and not limited to television programs. It was found that 42.5% of respondents believe that non-Muslim foreign media channels incite violence and hatred, while 28.5% believe that Muslim media channels are the ones who attend violence and hatred. Arabic incites violence and hatred.